Processo penal democrático e ministério público investigador - Canto Neto, Eduardo Olavo Neves (2018)
The text basically intends to demonstrate the importance of criminal investigation as an almost always present antecedent of the criminal prosecution in a Democratic State of Law. Based on an interpretation compatible with the constitutional principles, especially with regard to the double face of proportionality and its positive guarantee bias, it was sought to review the main criminal procedural postulates contained in the Major Law. In the sequence, the concept of the criminal investigation activity was approached, approaching its historical aspects, without neglecting its characteristics and purposes. Continuous, it was the origins of the Public Ministry, exclusive holder of the public criminal action, as well as of its structure in the exterior and in Brazil. In this line, considering the current formatting of Parquet, aimed at solving issues relevant to society without the need to be provoked to that extent, notes were drawn up on opposing theses and favorable to ministerial research. In order to bring some concreteness to the ideas exposed, mechanisms of obtaining evidence were indicated, with a brief analysis of those most used in the investigative activity. During the course, there were also brief considerations about the procedural systems, always with the eyes focused on the investigation by the Public Prosecution Service. The objective, quite honestly, was to present a critical and consistent view of the Brazilian reality, including what it says about the limitations that reach the organs in the provision of public services of undoubted relevance